Physical and electrical properties enhancement of rare-earth doped-potassium sodium niobate (KNN): A review - Mohd Hatta, Maziati Akmal; Abd Rashid, Mohd Warikh M.; Haji Azlan, Umar Al-Amani (2015)
Alkaline niobate mainly potassium sodium niobate, (KxNa1-x) NbO3 (abreviated as KNN) has long attracted attention as piezoelectric materials as its high Curie temperature (Tc) and piezoelectric properties. The volatility of alkaline element (K, Na) is, however detrimental to the stoichiometry of KNN, contributing to the failure to achieve high-density structure and lead to the formation of intrinsic defects. By partially doping of several rare-earth elements, the inherent defects could be improved significantly. Therefore, considerable attempts have been made to develop doped-KNN based ceramic materials with high electrical properties. In this paper, these research activities are reviewed, including dopants type and doping role in KNN perovskite structure.